2000
DOI: 10.1063/1.1314377
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corrugation on the quantum dynamics of dissociative and diffractive scattering of H2 from Pt(111)

Abstract: We present results of two dimensional ͑2D͒ and three dimensional ͑3D͒ calculations for dissociative and diffractive scattering of H 2 from Pt͑111͒, using a potential energy surface obtained from density functional theory ͑DFT͒ employing the generalized gradient approximation ͑GGA͒ in conjunction with a slab representation of the metal surface. The present study is motivated by the importance of Pt as a hydrogenation catalyst, and by a paradox regarding the amount of corrugation of the H 2 ϩPt͑111͒ potential en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…2 Out-of-plane diffractive scattering may well account for much of the ''lost flux'' observed in their experiments. 2 Like previous studies, [31][32][33] the present calculations indicate that experiments only looking at in-plane diffraction are not well suited for probing the corrugation of the molecule-surface PES.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2 Out-of-plane diffractive scattering may well account for much of the ''lost flux'' observed in their experiments. 2 Like previous studies, [31][32][33] the present calculations indicate that experiments only looking at in-plane diffraction are not well suited for probing the corrugation of the molecule-surface PES.…”
Section: Discussionmentioning
confidence: 59%
“…This controversy has been addressed in several theoretical studies [31][32][33] on H 2 scattering from Pt͑111͒. In a study treating all six molecular degrees of freedom quantum mechanically 33 and employing a PES based on density functional theory ͑DFT͒, 34,35 it was found that reaction does not obey normal energy scaling, and that the diffraction is substantial, supporting the conclusion of Luntz et al 12 It was suggested that the experiments by Cowin et al 1,2 failed to find proof of the corrugation of the surface because they measured only in-plane diffraction and did not consider diffraction out of the plane of incidence ͑the out-of-plane diffraction was predicted to be substantial by the theory͒.…”
Section: Introductionmentioning
confidence: 99%
“…For H 2 ϩPt(111), vibrational energy release is due to a decrease of the force constant associated with the H 2 vibration as the molecule approaches the barrier. 1 The same mechanism is responsible for the vibrational enhancement of reaction in the early barrier system H 2 ϩPd(100). 15 The same mechanism is also responsible for the efficient reaction of vϭ0 H 2 at low energies.…”
Section: Resultsmentioning
confidence: 99%
“…This controversy was also addressed in a previous paper 1 on H 2 ϩPt(111) where results of two-dimensional ͑2D͒ and three-dimensional ͑3D͒ calculations were presented. In the 3D calculations a model was employed in which the molecular degrees of freedom were the center-of-mass distance to the surface Z, the internuclear distance r, and one translational degree of freedom parallel to the surface x.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation